2006
DOI: 10.1097/01.brs.0000228722.12968.d2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Two-School-Year Multifactorial Back Education Program in Elementary Schoolchildren

Abstract: The intervention resulted in improved postural aspects related to spinal loading. The long-term effect of improved postural behavior at young age on back pain prevalence later in life is of interest for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 27 publications
5
57
2
6
Order By: Relevance
“…Considering a last limitation, the possible influence of confounding factors unrelated to the back posture intervention was carefully controlled during the 2-year interval of back posture education in elementary schoolchildren [13]. In the present evaluation at secondary school age, possible interfering factors related to the intervention program were not controlled.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Considering a last limitation, the possible influence of confounding factors unrelated to the back posture intervention was carefully controlled during the 2-year interval of back posture education in elementary schoolchildren [13]. In the present evaluation at secondary school age, possible interfering factors related to the intervention program were not controlled.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, self-reported postural behavior in youngsters' daily activities was investigated in relation to a biomechanical favorable postural lifestyle (removed sentence). Based on our previous study [13], immediate intervention effects of multi-factorial school-based back posture program included improved general and specific back posture knowledge. The current study demonstrated for the 2 years following after completion of the back posture program an increase of back posture knowledge in both conditions, but at a higher level for the children who had received the back posture program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to financial issues, only a few schools have the opportunity to buy such ergonomic furniture. Therefore several authors (Fedewa and Erwin, 2011;Frères and Mairlot, 2002;Wu et al, 1998) have simply suggested adding a triangular pelvic support on the chair to facilitate the opening of the trunk-thighs angle and consequently the anterior tilt of the pelvis and the physiological curves of the spine. Others authors have also recommended the use of a disc inflated with air to increase dynamism in SP (Erwin et al, 2016;Fedewa and Erwin, 2011;Gregory et al, 2006).…”
Section: Introductionmentioning
confidence: 99%